Teori Feminisme: Peran Perempuan Yang Bekerja Keras Dalam Keluarga di Era Modern - Saniria Benu; Andrian Wira Syahputra (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Nowadays, women do a lot of housework, reflecting a major shift in gender roles. In the past, women were more focused on family duties in patriarchal societies. However, today women also contribute to the professional world, often becoming the backbone of the family. The purpose of writing this article is to find out about the role of women who work hard in the family to meet family needs. This study uses a qualitative approach with a literature study to explore feminist theories and related literature that discuss the role of women in the family. The results of the study show that the role of women in the family has now developed into more than just a housewife; they also function as double workers who contribute to the family economy, both in the formal and informal sectors. Although involved in financial decision-making and earning a living, women often face challenges in balancing careers and household responsibilities, which can cause stress and fatigue. Therefore, it is important to have fairness in the division of tasks so that women can focus on their careers without being burdened by domestic responsibilities, while also being a role model for future generations in teaching the values ​​of gender equality and the importance of collaboration in the family.